La formación del autocuidado y seguridad personal en la práctica de juegos en niños y niñas de 4 años en la Unidad Educativa Américo Vespucio parroquia Ximena año lectivo 2015 - 2016 - Ortega Sánchez, Tatiana Denisse (2016)
THIS RESEARCH STARTED FROM THE OBSERVATION THAT MANY CHILDREN SHOW, IN SMALL OR LARGE SCALE, PROBLEMS IN SELFCARE AND PERSONAL SECURITY, THIS IS A DIFFICULT SITUATION FOR EDUCATORS AND PARENTS WHO OFTEN CAN’T IDENTIFY SUCH PROBLEMS IN THE KIDS AND CHOOSE THE EASIEST WAY WICH IS: IGNORE AND DON’T GIVE THE IMPORTANCE OF THE MATTER, SIMPLY, DOING NOTHING. WITH THIS SITUATION WE CAN IMPLEMENT THE GAME, WICH TODAY IS ONE THE MOST IMPORTANT AND EFFECTIVE TOOL FOR LEARNING AND FOR THE DEVELOPMENT OF CHILDREN, SO WE CAN’T RULE OUT THE USE OF THIS STRATEGY FOR THE SAKE OF THOSE CHILDREN, WHOM ARE PART OF OUR LIVES. FROM THIS POINT OF VIEW WE HAVE SEEN INTERESTING WAYS TO USE GAMES AS A METHODOLOGICAL STRATEGY, FOR EXAMPLE, A GAME PLAN AIMED TO COUNTER THE LACK OF SELF-CONTROL IN 4 YEARS OLD CHILDREN AT EDUCATIONAL UNIT “AMERICO VESPUCIO’……